Occurrence, toxic effects, and mitigation of pesticides as emerging environmental pollutants using robust nanomaterials – A review. (April 2022) - Intisar, Azeem; Ramzan, Arooj; Sawaira, Tehzeeb; Kareem, Ama Tul; Hussain, Nazim; Din, Muhammad Imran; Bilal, Muhammad; Iqbal, Hafiz M.N.
Abstract: Increasing demand of food and agriculture is leading us towards the increasing use and introduction of pesticides to the environment. The upright increase of pesticides in water and associated adverse effects have become a great point of concern to develop proficient methods for their mitigation from water. Various different methods have been traditionally employed for this purpose. Recently, nanotechnology has turned out to be the field of prodigious interest for this purpose, and various specific methods were developed and employed to remove pesticides from water. In this study, nanotechnological methods such as adsorption and degradation have been thoroughly discussed along with their applications and limitations where different types of nanoparticles, nanocomposites, nanotubes, and nanomembranes have played a vital role. However, in this study the most commonly adopted method of adsorption is considered to be the better technique due to its low cost, efficiency, and ease of operation. The adsorption kinetic models were described to explain the efficiency of the nano-adrsorbants in order to evaluate the mass transfer processes. However, various degradation methodologies including photocatalysis and catalytic reduction have also been elaborated. Numerous robust metal, metal oxide and functionalized magnetic nanomaterials have been emphasized, categorized, and compared for the removal of pesticides from water. Additionally, current challenges faced by researchers and future directions have also been provided. Highlights: Point and non-point sources of pesticides as emerging environmental pollutants. Adverse toxicological impacts associated with the pesticides are given. Nanomaterials-assisted remediation of pesticides are discussed. Functional nanostructured materials to mitigate pesticides are reviewed.